Polystyrene-Based Hydroxide-Ion-Conducting Ionomer: Binder Characteristics and Performance in Anion-Exchange Membrane Fuel Cells - Chae, Ji Eon; Lee, So Young; Yoo, Sung Jong; Kim, Jin Young; Jang, Jong Hyun; Park, Hee-Young; Park, Hyun Seo; Seo, Bora; Henkensmeier, Dirk; Song, Kwang Ho; Kim, Hyoung-Juhn (MDPI, 2021)
Polystyrene-based polymers with variable molecular weights are prepared by radical polymerization of styrene. Polystyrene is grafted with bromo-alkyl chains of different lengths through Friedel-Crafts acylation and quaternized to afford a series of hydroxide-ion-conducting ionomers for the catalyst binder for the membrane electrode assembly in anion-exchange membrane fuel cells (AEMFCs). Structural analyses reveal that the molecular weight of the polystyrene backbone ranges from 10,000 to 63,000 g mol(-1), while the ion exchange capacity of quaternary-ammonium-group-bearing ionomers ranges from 1.44 to 1.74 mmol g(-1). The performance of AEMFCs constructed using the prepared electrode ionomers is affected by several ionomer properties, and a maximal power density of 407 mW cm(-2) and a durability exceeding that of a reference cell with a commercially available ionomer are achieved under optimal conditions. Thus, the developed approach is concluded to be well suited for the fabrication of next-generation electrode ionomers for high-performance AEMFCs.